Development of Photovoltaic Energy in EU Countries as an Alternative to Fossil Fuels - Radosław Wolniak; Bożena Skotnicka-Zasadzień (Energies, 2022)
The aim of the article is to present the development of photovoltaic energy in the EU countries as one of the alternatives to fossil fuels. The article was prepared on the basis of secondary information and statistical data on the photovoltaic energy market in EU countries, and three hypotheses were formulated: H1—There is a statistically significant correlation between a country’s long-term orientation and its use of photovoltaic energy in European Union countries; H2—There is a statistically significant correlation between GDP per capita and photovoltaic energy use in European Union countries; and H3—There is a relationship between climate and photovoltaic energy use in European Union countries. Correlation coefficients and the Guilford classification were used to analyse the data. Data analysis has shown that photovoltaic energy is the second fastest-growing energy source in the EU, after wind energy. In 2020, 134 TWh of solar energy was produced in the EU countries. Based on the analysis, it can be concluded that there is a statistically significant correlation between the production of photovoltaic energy per person and the level of GDP per capita in the EU countries (Hypothesis 2). Germany and the Netherlands produce the most solar energy. The studies did not confirm Hypothesis 3; however, it can be seen that countries such as Germany, Belgium and the Netherlands have the highest PV energy efficiency compared to average temperature values. A data analysis showed statistically significant correlations between the country’s long-term orientation in the use of photovoltaic energy (Hypothesis 1). In the case of Germany and Belgium, the long-term orientation indicator is very high above 80, while Portugal, Poland and Finland have the lowest indicator, from 30 to 40.